Factors That Most Considered In Determining The Green Trust And Green Buying Interest - Mahfuz, H. Edy; Zulfikar, Rizka (International Journal of Educational Research & Social Sciences, 2022)
This study aims to examine the factors that are most considered by the community in determining trust and buying interest in green products. This research is a qualitative-quantitative descriptive study using a questionnaire as an instrument. The population and sample used in this study were the people of the city of Banjarmasin, South Kalimantan as many as 150 respondents using the non-purposive sampling method. The analysis technique used is quantitative descriptive analysis and average comparison analysis. This study examines 6 factors consisting of (1) Trust in objects, (2) Trust in Attributes, (3) Trust in Benefits, (4) Interest in buying transactionally, (5) Interest in Buying Referrals, (6 ) Interest in Preference (Preferential) and (7) Level of Curiosity (Explorative). The results of the study found that: (1) the level of trust and buying interest of the people of the city of Banjarmasin towards green products was in the medium category; (2) The factor of trust variable which is considered more dominant for respondents to consider based on the results of the highest average rating is trust in attributes (Price and Promotion) followed by trust in objects (Appearance and Quality), and trust in benefits (environment and health). (3) The factors of buying interest which are considered more dominant for the public to consider are referential, followed by preferential factors, exploratory factors and transactional factors.